Outbreak of idiopathic erysipelas in a psychiatric hospital. Issue 5956 (1st March 1975) - Dowsett, E G; Herson, R N; Maxted, W R; Widdowson, J P
Abstract : In an outbreak of idiopathic erysipelas ten women patients, aged 42-74, in a long-stay unit of a psychiatric hospital were simultaneously affected. Group A streptococci M-type 1 were isolated from two isolated from two patients with erysipelas and 18 carriers, but subsequent serological tests for type-specific antibody, antistreptolysin O, and anti-deoxyribonuclease B showed that the infection had been widespread in the unit. Treatment with ampicillin proved ineffective and to prevent relapse it was substituted by a standard course of intramuscular penicillin. This seems to be the first epidemic of this type to be reported and certainly the first outbreak of idiopathic erysipelas to be investigated by modern serological techniques.